2018
DOI: 10.36397/emteia.v9i1.235848
|View full text |Cite
|
Sign up to set email alerts
|

Linguagem Natural e Formal na Semiosfera da Aprendizagem Matemática: o caso da Geometria para a formação do Pedagogo

Abstract: Estudos dão conta da fragilidade da formação matemática do professor pedagogo, em particular, essa fragilidade acentua-se ainda mais para o caso da geometria. Tal formação insuficiente influencia diretamente o processo de ensino e aprendizagem da geometria nos anos iniciais do ensino fundamental que é o momento inicial de preparação para o desenvolvimento do olhar, imprescindível à aprendizagem da geometria. Nesse trabalho pretendeu-se discutir, a partir da Semiosfera do Olhar que é um espaço que congrega dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Thus, geometry teaching in schools is still timid, recalling some contagion with the "geometric omission", a phenomenon initially discussed by Lorenzato (1995). Furthermore, research indicates that the minimum about geometry is addressed in the classroom and that several teachers do not feel comfortable teaching it, especially in the early years of elementary school, with repercussions in the final years and high school (Moretti, 2017;Pereira da Costa & Rosa dos Santos, 2017). Silva and Silva (2014) showed that teachers are usually not confident when teaching geometric content.…”
Section: Contexts Involving Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, geometry teaching in schools is still timid, recalling some contagion with the "geometric omission", a phenomenon initially discussed by Lorenzato (1995). Furthermore, research indicates that the minimum about geometry is addressed in the classroom and that several teachers do not feel comfortable teaching it, especially in the early years of elementary school, with repercussions in the final years and high school (Moretti, 2017;Pereira da Costa & Rosa dos Santos, 2017). Silva and Silva (2014) showed that teachers are usually not confident when teaching geometric content.…”
Section: Contexts Involving Geometrymentioning
confidence: 99%
“…In this regard, authors such as Pavanello (1989), Passos (2000), Pereira (2001), Silva and Silva (2014), Moretti (2017), Pereira da Costa and Rosa dos Santos (2017), and Pereira da Costa (2019), among others, have been carrying out research in recent decades. Discussions on how geometric concepts are addressed in basic education and mathematics teacher education courses have revealed that, despite the progress achieved with debates on the subject, a certain fragility still prevails in this teaching area.…”
Section: Introductionmentioning
confidence: 99%
“…al. 1995;CURI, 2004;VASCONCELLOS, 2008;FURLANETTO, 2013;SCHIRLO;RUTZ DA SILVA, 2013;MORETTI, 2018;ZORTÊA, 2018) indicam em seus resultados que professores formados em Pedagogia apresentam lacunas conceituais referentes ao conhecimento matemático em todos os eixos do currículo, tais como: Números e Operações; Pensamento Algébrico; Espaço e Forma/Geometria; Grandezas e Medidas e Tratamento da Informação/Estatística e Probabilidade. Para esses pesquisadores, o campo mais fragilizado é o da Geometria.…”
Section: A Linguagem Matemática Nas Aulas De Geometriaunclassified
“…Como Duval (2011, p. 85) É necessário perceber que esses olhares se articulam em função da visão icônica e não icônica. Moretti (2013) apresenta um esquema para ilustrar essa articulação, aqui representado na Figura 2.…”
unclassified